Makna Pluralitas Dalam Film â€œRaya And The Last Dragonâ€ (Studi Analisis Semiotika Roland Barthes) - Pujianti, Inne; Mulyana, Ahmad (Syntax Literate, 2024)
Film is actually a text that shows social reality. The text contained in a film forms a meaning as well as reflects a certain culture. The messages conveyed in films can be informative as well as educational media for the audience, messages to introduce a culture, build a democratic society and films can also unite differences and construct social realities that occur in society. The author in this study looks at the differences in the meaning of pluralism in the film "Raya and The Last Dragon". That there is a fact that a film can carry out the function of improving people's lives with the story line with the diversity that exists and the characteristics of the differences depicted in the film. This study aims to find out the various meanings in terms of designation, implied and myths contained in the film "Raya and the Last Dragon". The writing in this study uses a constructive paradigm to carry out Roland Barthes' semiotic analysis and this research uses qualitative research methods to understand the various meanings in the film "Raya and the Last Dragon". Based on the results of research and discussion, it can be said that this film shows the meaning of pluralism which is understood democratically, equality of difference. the differences that are denotatively described have connotations associated with the differences that are constructed into an agreement. The film depicts togetherness and unity in a difference, so that a myth arises that describes a shift in meaning from plurality, namely that strength and unity are formed from differences and diversity that exist.